(untitled) - Schena, Mark Schena (Hoboken, NJ, 2003)
This authoritative text begins with an introduction to basic microarray technology. The author then provides clear explanations of the conceptual and theoretical basis of this technology, followed by thorough and multi-disciplinary coverage of modern and emerging applications. The coverage includes chapters on microarray informatics, gene expression profiling, genetic diagnostics, and novel microarray technologies.
Keywords: DNA microarrays.,Protein microarrays.,Vi mạng DNA